2013
DOI: 10.1021/ic4019025
|View full text |Cite
|
Sign up to set email alerts
|

Pentanuclear Heterometallic {Ni2Ln3} (Ln = Gd, Dy, Tb, Ho) Assemblies. Single-Molecule Magnet Behavior and Multistep Relaxation in the Dysprosium Derivative

Abstract: The reaction between Ln(III) chloride and NiCl2·4H2O salts in presence of a multidentate sterically unencumbered ligand, (E)-2,2'-(2-hydroxy-3-((2-hydroxyphenylimino)methyl)-5-methylbenzylazanediyl)diethanol (LH4) leads to the synthesis of four isostructural pentanuclear hetereometallic complexes [Ni2Dy3(LH)4]Cl (1), [Ni2Gd3(LH)4]Cl (2), [Ni2Tb3(LH)3(LH2)]Cl2 (3), [Ni2 Ho3 (LH)3 (LH2)]Cl2 (4) with unprecedented topology. Here the two compounds 1 are 2 are monocationic and crystallize in chiral space group, P2(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 69 publications
6
47
0
Order By: Relevance
“…From the knowledge base of Ni–Ln compounds, synthetic methods offer a variety of topology with different levels of control in the design. To the best of our knowledge, only six pentanuclear Ni–Ln heteronuclear complexes, (Figure ) are found whose detailed magnetic analysis has been done. Although the spirocyclic core is well known in pure 4f based compounds, the case of coordination compounds based on 3d‐4f systems, it is scare.…”
Section: Resultsmentioning
confidence: 99%
“…From the knowledge base of Ni–Ln compounds, synthetic methods offer a variety of topology with different levels of control in the design. To the best of our knowledge, only six pentanuclear Ni–Ln heteronuclear complexes, (Figure ) are found whose detailed magnetic analysis has been done. Although the spirocyclic core is well known in pure 4f based compounds, the case of coordination compounds based on 3d‐4f systems, it is scare.…”
Section: Resultsmentioning
confidence: 99%
“…Our research group has been investigating the metalation behavior of the phosphorus‐supported tris‐hydrazone ligand, S=P[N(Me)N=CH‐C 6 H 3 ‐2‐OH‐3‐OMe] 3 (LH 3 ) with transition‐metal/lanthanide ions and has found that 3d homotrimetallic5 and 3d‐4f heterotrimetallic6 compounds can be readily prepared by using this family of ligands, many of which are SMMs. Also, through the use of compartmental ligands we have assembled [Cu II Ln III ],7a [Cu II 5 Ln III 2 ],7b [Ni II 2 Ln III 3 ],7c [Zn II /Ln III ],7d [Co II 2 Ln III ],7e and [Mn III 2 Ln III 2 ]7f complexes. Recently, the use of 6‐formyl‐2‐(hydroxymethyl)‐4‐methylphenol (LH 2 ) allowed us to assemble the first examples of heterometallic pentanuclear Co II 4 Ln III complexes 8.…”
Section: Introductionmentioning
confidence: 99%
“…As aforementioned, complexes 6 and 7 display the field-induced SMM behaviors. Most of Ni II -Ln III complexes behaving as SMMs contain paramagnetic Ni II ions, however, the Ni II -Ln III system that exhibits the highest energy barrier ever found is a {Ni 3 Dy 2 } cluster complex [31] in which the Ni II ions, as our compounds, are diamagnetic. Compared with the similar works using achiral Schiff-base ligands [23a], we investigate the ac properties of target complexes in details.…”
Section: Magnetic Propertiesmentioning
confidence: 84%